Investigation of the plasma characteristics of a low pressure Grimm-type glow discharge - Ferreira, Nicolaas Phillipus (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1980.